Technique of formation of system of retail trade of the city district - I. A. Grigoryants (Вестник СибАДИ)
The article presents the basic problem points in the system of retail trade city district on the example of Samara city. Using regulatory data and legislative acts the author offers the method of calculation of the minimum security of the urban district area of commercial properties. On the basis of this technique we propose an algorithm for the minimum security of the population of the city of Samara area trade sites for a five-year period. To build this methodology and algorithm were used such indicators as the resident population of the urban district, the turnover of retail trade per capita, other socio-economic indicators of living standards.